(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Mangrove ecosystems have forest functions and benefits as a nursery zone for fisheries biota, protecting coastal abrasion, carbon sinks, and supporting nutrient content for aquatic health. Unfortunately, the area of this forest is decreasing, so conservation efforts are needed. Mangrove forests in Wakatobi Regency are a very important resource for coastal areas and small islands and should be preserved and continuously developed, along with other resources. Mangrove forest conservation efforts have become the main concern of the parties. However, planting and rehabilitation efforts are still an obstacle due to very slow growth and even death. Several cases were found where mangrove propagule planting on Wangi-Wangi Island Beach died in a short time. The aim of the research is to design a prototype or simple technology that is useful for trapping sediment and reducing the influence of waves at the beginning of propagule planting and when mangrove saplings have begun to grow and survive at the age of about 1.5 to 3 years. This research is included in quantitatively applied research in the form of a simple structural product that is then installed on Melaione Matahora Beach and Liya Togo Beach. The results obtained are the design (prototype) of a mangrove trap with a concrete structure measuring as 1 m x 0,5 m x 0,5 m with a shape similar to a puzzle box, each side of which locks together. Wakatobi mangrove trap box contains a mixture of mangrove leaf litter, seagrass litter, aggregate humus soil, and sandy soil, which is then planted with propagules of mangrove. This research lasted approximately 1 (one) year more, and the mangrove-planted seedlings grew well, although seedlings planted on Melaione Matahora Beach initially died due to moss pests, but after repairing the prototype to the 1st generation model, the propagule grew well and survival until now.